Glucose transport 1 deficiency presenting as infantile spasms with a mutation identified in exon 9 of - Hyun Hee Lee; Yun Jung Hur (Korean Pediatric Society, 2016)
Glucose transport 1 (GLUT-1) deficiency is a rare syndrome caused by mutations in the glucose transporter 1 gene (SLC2A1) and is characterized by early-onset intractable epilepsy, delayed development, and movement disorder. De novo mutations and several hot spots in N34, G91, R126, R153, and R333 of exons 2, 3, 4, and 8 of SLC2A1 are associated with this condition. Seizures, one of the main clinical features of GLUT-1 deficiency, usually develop during infancy. Most patients experience brief and subtle myoclonic jerk and focal seizures that evolve into a mixture of different types of seizures, such as generalized tonic-clonic, absence, myoclonic, and complex partial seizures. Here, we describe the case of a patient with GLUT-1 deficiency who developed infantile spasms and showed delayed development at 6 months of age. She had intractable epilepsy despite receiving aggressive antiepileptic drug therapy, and underwent a metabolic workup. Cerebrospinal fluid (CSF) examination showed CSF-glucose-to-blood-glucose ratio of 0.38, with a normal lactate level. Bidirectional sequencing of SLC2A1 identified a missense mutation (c.1198C>T) at codon 400 (p.Arg400Cys) of exon 9.